Ultrastructural characteristics of neocortex in rats with alloxan hyperglycaemia under application of citicoline. - Zhylyuk, V. I.; Mamchur, V. I.; Tverdokhleb, I. V.; Petruk, N. S. (Морфологія / Morphologia / Morfologìâ, 2013)
Background. Diabetes mellitus is known to be associated with pathological changes in the CNS, which may serve as a primary cause in the occurrence of cognitive deficit and increase the risk of cerebrovascular complications. At the same time, pharmacological neuroprotection is one of the key directions in the treatment of cerebrovascular disorders of various origins. Objective. To determine the extent of ultrastructural changes in the cerebral cortex of rats with chronic hyperglycemia in experimental therapy with citicoline. Methods. The research was conducted on 18 white rats divided randomly in 3 groups: group 1 – intact animals; group 2 – rats with alloxan diabetes; group 3 – rats with alloxan diabetes + citicoline 500 mg/kg. Diabetes mellitus was induced in rats by a single intraperitoneal injection of alloxan monohydrate (150 mg/kg). Citicoline was administered intragastrically once per day during 20 days from the 11th day after alloxan injection. Transmission electron microscopy was performed on the 20th day of citicoline administration. Results. Course administration of citicoline improves the condition of neuronal and glial cells, reduces the severity of disturbance in myelin nerve fibers, increases the packing density of synaptic vesicles and stabilizes the structure of the presynaptic and postsynaptic membranes of neocortex in rats with alloxan diabetes. Conclusion. Conducted experimental studies confirm high neuroprotective potential of citicoline in diabetes mellitus.